2020
DOI: 10.3389/fped.2020.00192
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Domestic Pet Ownership, and the Risk of Pet Sensitization and Atopic Dermatitis in Preschool Children: A Prospective Birth Cohort in Shanghai

Abstract: Background: Although domestic pet ownership is on the rise, the impact of early life pet ownership on children's pet sensitization and atopic dermatitis (AD) remains controversial. Methods: Shanghai Allergy Cohort is an ongoing prospective study followed up to the age of 5 years. Pregnant mothers were recruited and their offspring were followed up every year by a group of pediatricians. Information on furred pet ownership was collected by the questionnaire. AD was diagnosed by dermatologists according to disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
(40 reference statements)
0
10
0
1
Order By: Relevance
“…We found no strong evidence for an association between cat or dog ownership and allergic sensitization to the respective allergen, suggesting that ownership is unlikely to be the main determinant of cat-and dog-specific allergic sensitization; instead, other factors such as genetic susceptibility are likely decisive. Other cohort studies examining associations of pet ownership with allergic sensitization to associated allergens have been conflicting, with some reporting a positive association 72,73 and others reporting either no 20,[73][74][75][76][77][78] or an inverse association. 20,23,[78][79][80] These inconsistencies could be related to differences in the timing of assessment of allergic sensitization, because trajectories of pet-specific allergic sensitization have been observed to differ in pet owners versus in non-pet owners.…”
Section: Comparison With the Literature And Interpretation Of Resultsmentioning
confidence: 99%
“…We found no strong evidence for an association between cat or dog ownership and allergic sensitization to the respective allergen, suggesting that ownership is unlikely to be the main determinant of cat-and dog-specific allergic sensitization; instead, other factors such as genetic susceptibility are likely decisive. Other cohort studies examining associations of pet ownership with allergic sensitization to associated allergens have been conflicting, with some reporting a positive association 72,73 and others reporting either no 20,[73][74][75][76][77][78] or an inverse association. 20,23,[78][79][80] These inconsistencies could be related to differences in the timing of assessment of allergic sensitization, because trajectories of pet-specific allergic sensitization have been observed to differ in pet owners versus in non-pet owners.…”
Section: Comparison With the Literature And Interpretation Of Resultsmentioning
confidence: 99%
“…Misic and colleagues (2015) also reported microbiota sharing between cohabiting humans and pets (cats and dogs). Exposure to dogs in early life has been associated with decreased risk of atopic dermatitis (Li et al ., 2020), and exposure to a dog before and during pregnancy has been shown to decrease the risk of food allergy in the first year of life, which the authors suggest may be due to the beneficial effects of the dog's microbes (Smejda et al ., 2020). The beneficial effect arising from dogs in the home may be a consequence of immune modulation following exposure to a more diverse microbiota.…”
Section: Colliding and Interacting Microbiomes And Microbial Communitiesmentioning
confidence: 99%
“…It is worth noting that the incidence of murine typhus, transmitted to humans from mice by fleas infected with Ricketsia typhi , is highest in the proximity of major international seaports in Taiwan [ 47 ]. While pet dog ownership in Taiwan and China has become very popular in recent years [ 48 ], and while an initial retrospective study suggested that dog owners were at increased risk of developing breast cancer [ 49 ], this observation has not been confirmed in a larger prospective study [ 50 ]. As we suggested previously, direct fecal-oral transmission from mice to humans seems more likely [ 16 ].…”
Section: Discussionmentioning
confidence: 99%